Main The Principle of Inter-Religious Tolerance: A Comparative Study of The Interpretation of Surat Al Kafirun Between Hamka and Quraish Shihab - Yumna Irbah; Anisah Nur Syahidah (Bulletin of Islamic Research, 2023)
All religious people yearn to live in peace in a multi-religious and belief community. However, harmony and harmony between religious communities can be realized by mutual respect for tolerance. Without tolerance, inter-religious harmony is difficult to occur. So tolerance is a condition for the realization of harmony itself. This study aims to find out about the principle of inter-religious tolerance in Surat al-Kafirun according to the interpretation of Hamka and Quraish Shihab. This type of research is library research. The method used is descriptive comparative analysis method. The approach used is a descriptive, interpretative, and comparative approach. The result of this study is that there is a common opinion between Hamka and Quraish Shihab regarding the principle of inter-religious tolerance, namely that it is impossible to combine Islam with other religions. And every religion can carry out worship according to beliefs and there is no compulsion to believe in each other's teachings. Meanwhile, the difference lies only in the delivery and the way of explaining the interpretation of each mufassir. In Hamka's commentary on al-Azhar, al-Kafirun's letter is explained more concisely and Hamka refers to the interpretations of other scholars such as Al-Qurthubi, Sheikh Muhammad Abduh, and Ibn Kathir. Whereas Quraish Shihab explains the letter al-Kafirun in the book of interpretation of al-Misbah more thoroughly, Quraish Shihab includes another verse in the Qur'an which has the same content as the letter al-Kafirun to explain further the meaning of the letter al-Kafirun, as well as in his interpretation Quraish Shihab also explains the position of the words from sura al-Kafirun to find out the different meanings of each verse.